1979
DOI: 10.1093/bja/51.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Labetalol in Controlled Hypotension

Abstract: A study of controlled hypotension was undertaken in 50 major surgical patients using labetalol, a drug with both alpha- and beta-adrenoceptor blocking activity. The patients were such that difficulty in achieving controlled hypotension could be anticipated: the young, the anxious and those for whom halothane was contraindicated. The administration of labetalol quickly induced hypotension which was controlled easily and was rapidly antagonized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Continuous ECG monitoring revealed no adverse changes in any of these ischaemic hearts, and there were no post-operative sequelae (Cope & Crawford, 1979). Reversal of the hypotension in all cases was readily achieved by the intravenous administration of atropine sulphate 0.6 mg, systolic BP rapidly returning to a near normal level.…”
Section: Resultsmentioning
confidence: 74%
“…Continuous ECG monitoring revealed no adverse changes in any of these ischaemic hearts, and there were no post-operative sequelae (Cope & Crawford, 1979). Reversal of the hypotension in all cases was readily achieved by the intravenous administration of atropine sulphate 0.6 mg, systolic BP rapidly returning to a near normal level.…”
Section: Resultsmentioning
confidence: 74%
“…One must be cautious in applying the results of our study to man. The doses of labetalol needed to establish arterial hypotension in dogs anaesthetized with pentobarbitone and fentanyl were much larger than those used in earlier studies in man (Scott et al, 1978;Cope and Crawford, 1979). In spite of these high doses, however, haemodynamic changes were minimal and perfusion was well maintained.…”
Section: Table II Fractional Distribution Of Cardiac Output and Indimentioning
confidence: 74%
“…Labetalol (Glaxo Laboratories) possesses both alpha-and beta-adrenergic blocking properties (Farmer et al, 1972). Its use in hypotensive anaesthesia has been reported by Scon and others (1978) and Cope and Crawford (1979) who obtained a satisfactory decrease in arterial pressure unaccompanied by tachycardia in patients anaesthetized with halothane. Changes in regional blood flow during deliberate hypotension with labetalol have not been reported.…”
mentioning
confidence: 87%
“…As nitroprusside is not devoid of adverse effects such as tachycardia, tachyphylaxis, increased intrapulmonary shunt (3), and cyanide toxicity (4), the search for other useful agents has continued. Labetalol, an aand Padrenergic blocking agent, in combination with various inhalation anesthetics, has been advocated for the induction of hypotension (5)(6)(7)(8)(9). Although it has been suggested that labetalol, when used to produce deliberate hypotension, may not increase intrapulmonary shunting, there is insufficient evidence to support this.…”
Section: Pharmacology Nitroprussidementioning
confidence: 99%